Chronology of the Qur'an According to Theodor Nöldeke and Sir William Muir (Analysis of the History of the Qur'an and Life of Mahomet) - Ahmad Syukron; Nikmatul Khairiyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This article talked about the analysis of the chronology of the Qur'an perspective by Theodor Nöldeke and Sir William Muir in their books The History of the Qur'an and Life of Mahomet using a descriptive-comparative method. The chronology of the Al-Qur`an that was initiated by Theodor Nöldeke by using the theory of four periods revelations (three periods of Makkah and one period of Medina) were assessed as the attempts to make it easy for Western orientalist on how to study the Qur'an. However, not a few of western scholars criticized Nöldeke's chronology because it had several weaknesses including the division of three periods of Mecca which did not have a solid foundation, the inconsistency of the application of the characteristics letters, the incongruity with historical reality that was visible in the calendar of the sura Al-Fâtihah, and a decrease in the quality of the language style of The Al-Qur`an, even Nöldeke's chronology, was only categorized as letters based on the same characteristics that were not in the chronological order of the Qur'an. As for Sir William Muir, who composed the chronology of the Qur'an into six periods of revelation (five periods of Mecca and one the Medina period) was considered to be too ideological and viewed as radical because he determined the date of the group of letters he was dating as he called it a rhapsody letter, before the Prophet received the first revelation.